2022
DOI: 10.1021/acs.energyfuels.2c01355
|View full text |Cite
|
Sign up to set email alerts
|

Continuous CO2 Separation from a N2 + CO2 Gas Mixture Using Clathrate Hydrate: Insights into Sustainable Post-combustion Carbon Capture

Abstract: Clathrate-hydrate-based CO2 capture from a post-combustion N2 + CO2 gas mixture has been experimentally investigated for decarbonization. In this study, we performed hydrate-based continuous CO2 separation experiments for N2 + CO2 + tetrahydropyran (THP) + water system. The experimental conditions were set at 280.1 K under 3.0 MPa with THP mass fractions w THP of 0.22 and 0.11. For each experimental run, the time-dependent changes in compositions in the gas phase and the hydrate slurry were recorded hourly unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Fitting parameters for Equation(2) and the correlation coefficient Figure8shows the scatter of the three-phase equilibrium conditions in carbon dioxide + water system measured in this study with those reported in the previous studies. From this figure, we evaluated the even more precise external consistency of the measured data in this study with the data from the previous studies.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Fitting parameters for Equation(2) and the correlation coefficient Figure8shows the scatter of the three-phase equilibrium conditions in carbon dioxide + water system measured in this study with those reported in the previous studies. From this figure, we evaluated the even more precise external consistency of the measured data in this study with the data from the previous studies.…”
supporting
confidence: 61%
“…From this figure, we evaluated the even more precise external consistency of the measured data in this study with the data from the previous studies. pcalc is calculated with the interpolation of the three-phase equilibrium condition data measured in this study by using Equation(2). Dot line represents twice the uncertainty of the pressure measurement in this study.…”
mentioning
confidence: 99%
“…Gas hydrates could be used as a molecular sieve, whereby depending upon the shape and size of the hydrate-forming guests, one of the gases from a gas mixture may preferentially occupy the solid hydrate cages and become separated from its mixture. 41 A mini review by Wu et al 42 summarized the stateof-the art research work performed for hydrate-based gas separation for CO 2 capture from CO 2 /CH 4 gas mixtures. A bench-scale dual-bed cyclic gas hydrate process (DB-CGHP) for separation of gas mixtures was presented, and potential for industrial scale-up similar to a pressure swing adsorption process was demonstrated.…”
Section: ■ Simulationmentioning
confidence: 99%
“…A review by Rodionova et al discussed structures of single and double ionic clathrate hydrates (semi-clathrates) in the presence of different gases and possibilities of structural transition as a result of the presence of these gases. Gas hydrates could be used as a molecular sieve, whereby depending upon the shape and size of the hydrate-forming guests, one of the gases from a gas mixture may preferentially occupy the solid hydrate cages and become separated from its mixture . A mini review by Wu et al summarized the state-of-the art research work performed for hydrate-based gas separation for CO 2 capture from CO 2 /CH 4 gas mixtures.…”
Section: Applicationsmentioning
confidence: 99%
“…CO 2 also forms binary sII and sH hydrates under milder pressure and temperature conditions than pure CO 2 hydrate (1.2 MPa at 273 K) with the assistance of larger guest molecules, such as tetrahydrofuran (THF: C 4 H 8 O) and cyclopentane (CP: C 5 H 10 ). The large guests are encaged into the larger cages of the sII phase (H or 5 12 6 4 cages), and the CO 2 is encaged into the small D cages. Binary hydrates with THF, CP, , and tetrahydropyran (THP: C 5 H 10 O) , large guests have been studied as media to store gases such as H 2 , CH 4 , and CO 2 in their empty D cages. However, relatively little is known about the effect of these large guest molecules or synergistic effects between large and small guest molecules on the crystal structure and physical properties of clathrate hydrates under different temperature and pressure conditions.…”
mentioning
confidence: 99%